Can we explain managerial non‐answers during conference call Q&As? - Bamber, Matthew; Nappert, Pier‐Luc (Contemporary Accounting Research, 2025)
Abstract Management teams often avoid answering questions during conference call question and answer sessions (Q&As). Viewing this as an information asymmetry issue, accounting scholars have suggested that this behavior is ill‐advised and that non‐answers signal to investors the suppression of bad news. In this article, we demonstrate that this argument lacks nuance. Instead, we argue that answers and non‐answers necessarily coexist and are codependent. Our contribution stems from our social interactionist lens, whereby we draw on interdisciplinary perspectives of workplace silence to make sense of our data. We propose three explanations for managerial non‐answers, namely that they are used (1) defensively, (2) reflectively, and (3) negotiatively. Despite the seeming complexity, analysts claim they can make sense of what managers are able to say in this forum, and by extension, what they do (or perhaps, can) not. From here, we argue that analysts are socialized to managerial non‐answers. Despite this, there is general concern that investors allow an innate fear of “silence” to prejudice their judgment of non‐answers. Thus, we highlight a communication gap between management, intermediary, and investor. On the one hand, this implies a source of market inefficiency, but on the other it points toward a source of potential value in sell‐side analyst work, specifically, their experience and expertise in social interaction.